A scoping review of knowledge, attitudes, and practices in swine farm biosecurity in North America - Chepkwony, Maurine C.; Makau, Dennis N.; Yoder, Colin; Corzo, Cesar; Culhane, Marie; Perez, Andres; Perez Aguirreburualde, Maria Sol; Nault, André J.; Mahero, Michael (Frontiers in Veterinary Science, 2025)
Pork is one of the most popular consumer meat choices globally, second to poultry. In the past two decades, the rising demand in pork, has seen pig farming move toward intensive farming methods, characterized by high pig densities which is a risk for swift spread of disease necessitating proper and strict biosecurity adherence to facilitate disease-free conditions and business continuity. North America is the second largest pig producer globally. We conducted a review of available peer-reviewed original publications to scope for available data on the knowledge, attitudes, perceptions, and practices concerning biosecurity among swine producers in North America from the year 2011 to 2022 using the PRISMA-SCr guidelines. Out of the 323 papers that fit our search criteria, we present insights from the 18 papers that were relevant to our study. We summarize key findings on biosecurity practices and propose critical practices for biosecurity adherence. We also present our findings on the complexities that influence producers’ adoption of biosecurity plans and note variations in biosecurity strictness between states and how these are influenced by farm size and perceived disease risk. In conclusion, this review highlights the need for updated assessments of biosecurity practices, leveraging technology particularly machine learning, for risk assessment, and acknowledges the role that demographics and risk perception play in biosecurity adoption. Ultimately, effective biosecurity measures are imperative for safeguarding North American swine production systems against disease threats especially foreign animal diseases like the African swine fever (ASF), foot and mouth disease (FMD) and classical swine fever.